An Essay: 21st Century Curricular Construction Using 20th Century Tools, and Students' ICT Literacy. - Koudstaal, D.; Pugh, Roy (Key Centre for School Science and Mathematics, Curtin University of Technology, 2006)
Today western public education systems the world over are responding to the exponential growth in the use of the hypermedia and other related technologies. For example, in 1993, there were only 130 sites on the World Wide Web and only nine years later there were more than 9 million sites. In genera l, teachers and curriculum designers assume, in perhaps what has become a paradigmatic way, that young teenage students, exposed to technology and the hypermedia from an early age, will respond favourably if computers, the hypermedia and ITC are incorporated in curricula and classroom activities. Such assumptions may not necessarily be founded on sound observation or research, but at best on anecdotal evidence. Policymakers, educators, parents and employers might be deeply concerned that the education system as it has been appears not to prepare young people for our rapidly changing society. In this essay, we explore the promises of the newly designed curricula in Tasmania, years K to 10 and post compulsory 11 and 12, for making learning relevant to the 21st century, and whether this project might be impeded, unconsciously perhaps and not culpably, by our human tendencies to hold to traditional, tried and familiar theories of public education. These might include and be quite reminiscent of, for example, Tyler’s rationale which has had an enduring influence on Western theories of curriculum construction through the 20th century until now.In the new curricula, learning processes such as social responsibility and communication are deemed very important. Is it possible that we can assess students’ engagement in these learning processes with theories that derive learning objectives in ways that have been developed decades earlier, and are still accepted as theories of education? In what ways can we identify those theories that seem to be still tacitly espoused? Might it be inappropriate to package a 21st century curriculum in a 20th century Tyler-type curricular paradigm? What happens when new paradigms emerge? Might the emerging patterns of educators’ assumptions in relation to students’ ITC literacy and associated learning styles, for example, be strongly held, consistent and supported enough to be a new educational paradigm or might they still be simply assumptions governed by earlier paradigms? And if there is such a discernable new paradigm, what challenges for 21st century curriculum might this new paradigm invite?